PEMANFAATAN AMPAS KOPI SEBAGAI MATERIAL DASAR UNTUK MEMBUAT POT TANAMAN - Yunidar, Dandi; Hifzhurrahman, Ahmad Hafidzh (Narada : Jurnal Desain dan Seni, 2023)
As the culture of drinking coffee strengthens in various circles of Indonesian society, the amount of residual dregs produced from brewing coffee drinks is also increasing. The main objective of this design process is to find the right mixture composition to reprocess coffee grounds so that they can be used as a basic material for making ornamental plant pots. In finding the right dough composition, this design was carried out through a material exploration approach by mixing several other binders with coffee grounds. After going through 30 trials involving several ingredients such as coffee grounds, starch, vinegar, glycerol, water, jelly, and PVA (Polyvinyl Alcohol), this experiment succeeded in getting the right and ideal composition with characteristics resembling clay and easy to use. molded and does not crack easily when dry. As a result, this design process succeeded in producing an initial product in the form of a small plant pot for ornamental plants made from the dregs left over from brewing coffee drinks. This ornamental plant pot product is an initial stage product which at the next design stage can be developed into a more complex and attractive product.